2019
DOI: 10.21608/jvmr.2019.43340
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effect of age, breed and season on sexual behaviour, testosterone concentrations and scrotal circumference in Egyptian rams

Abstract: The objective of this study was to detect the influence of age, breed and season on sexual behaviour, testosterone concentrations and scrotal circumference in Egyptian rams. The study was carried out at agricultural research center belonging to Minia University, Shosha village, Samalut city, El-Minia. Ten crossbred and five adult Ossimi rams were used during this study. Every ram was allowed to breed two ewes to evaluate its sexual behaviour for a twenty minutes test. Blood samples were collected three times p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Similar findings were obtained by Mohamed et al (2016) who found that using rice straw treated with enzymes or effective microorganisms as energy sources in Ossimi ram lambs dietary were enhanced growth rate, testosterone level and sexual activity of ram lambs pre and at puberty. Hafez and Hafez (2013) and Mostafa and Farghal (2019) reported that testosterone hormone has a fundamental role in the reproductive behavior of rams and their secondary sexual characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were obtained by Mohamed et al (2016) who found that using rice straw treated with enzymes or effective microorganisms as energy sources in Ossimi ram lambs dietary were enhanced growth rate, testosterone level and sexual activity of ram lambs pre and at puberty. Hafez and Hafez (2013) and Mostafa and Farghal (2019) reported that testosterone hormone has a fundamental role in the reproductive behavior of rams and their secondary sexual characteristics.…”
Section: Discussionmentioning
confidence: 99%